Study on Hotel Employee Performance with Leadership Style, Organizational Culture and Discipline as Predictors at Patra Semarang Hotel & Convention - Umar Abdul Jabbar; Andhi Supriyadi (Badan Penerbit STIEPARI Press, 2025)
Patra Semarang Hotel & Convention is a suitable place to study. The mission of this research is to identify and explain the impact of leadership style, work culture, and discipline on employee productivity. The information in this study was collected through filling out a questionnaire. This research involved 80 participants. Descriptive and quantitative statistics are used to process the data obtained. Multiple regression analysis is used to assess the impact of independent variables on dependent variables, test models and hypotheses. Before analysis, validity and reliability were also checked. Regression analysis shows that employee performance is influenced directly or indirectly by leadership style, work culture and work discipline. In addition, these findings indicate that leadership style, work culture, and work discipline jointly influence employee performance. This shows that to improve employee performance, a good leadership style, positive work culture, and strong work discipline are very important.